ANALISIS TINGKAT KESEHATAN BANK BNI SYARIAH, TBK DENGAN MENGGUNAKAN METODE RGEC - Mamu, Mariani; A. O. Pelleng, Frendy; Kelles, Dantje (JURNAL ADMINISTRASI BISNIS (JAB), 2016)
Abstract. The purpose of this study to determine how the health level of PT Bank BNI Syariah, Tbk based health assessment methods bank continues to grow, the latest method is a method RGEC. using RGEC in 2012-2014. The soundness of banks measured by financial ratios. These ratios include CAR, NPA, ROA, ROE, NIM, ROA, FDR, NPL, LR, IRR, DR, and facr.This research is descriptive with quantitative approach. The subjects were financial statements of Bank Negara Indonesia Sharia. The objects used in this study are the financial statements of Bank Negara Indonesia Syariah 2012-2014.Data collection techniques in this research that is by downloading the financial statements of the official website of the State Bank Indonesia Sharia. The analysis technique used is the method RGEC to determine the soundness of a bank are classified into health ratings of banks.The results of this research note that for Rating Bank Negara Indonesia Syariah using RGEC shows predicate health of the bank in accordance with the standards set by Bank Indonesia, for the period of December 2012, December 2013, up to December 2014 the average Bank Negara Indonesia HEALTHY Sharia predicate, so that the performance of Bank Negara Indonesia Sharia should be maintained by preserving the soundness of banks. Bank Negara Indonesia Sharia can improve the ability of assets, capital management, as well as operating income, so the quality of bank profits can be maintained and even improved.